Layer-dependent excellent thermoelectric materials: from monolayer to trilayer tellurium based on DFT calculation - Zhang, Kexin; Yang, Rennong; Sun, Zhehao; Chen, Xihao; Huang, Sizhao; Wang, Ning (Frontiers in Chemistry, 2023)
The monoelemental two-dimensional (2D) materials, which are superior to binary and ternary 2D materials, currently attract remarkable interest due to their fascinating properties. Though the thermal and thermoelectric (TE) transport properties of tellurium have been studied in recent years, there is little research about the thermal and TE properties of multilayer tellurium with interlayer interaction force. Herein, the layer modulation of the phonon transport and TE performance of monolayer, bilayer, and trilayer tellurium are investigated at 300K. Firstly, it was found that the thermal conductivities as a function of layer numbers possess a robust unusual nonmonotonic behavior. Moreover, the anisotropy of the thermal transport properties of tellurium is weakened with the increase in the number of layers. By phonon-level systematic analysis, we find that the variation of phonon transport under the layer of increment is 2 determined by increasing phonon velocity in specific phonon modes. Then the TE transport properties show that the maximum figure of merit (ZT) reaches 6.3 (p-type) along the armchair at 700 K for the monolayer, and 6.6 (p-type) along the zigzag at 700 K for the bilayer, suggesting that the TE properties of the monolayer are highly anisotropic. This study reveals that monolayer and bilayer tellurium will have tremendous opportunities as candidates in TE applications. Moreover, the layer number further increasing to 3 will hinder the improvement of TE performance for 2D tellurium.